Analyzing Practice, Research, and Accountability Turns in Finnish Academic Teacher Education - Toom Auli; Husu Jukka (Springer, 2022)
This chapter considers the evolution of Finnish teacher education since it was placed into universities according to a political decision over 40 years ago. While being a part of scholarly community and academic university education, it has both internally and also externally undergone several changes and developments. Finnish universities and faculties of education are autonomous in providing research-based teacher education, and they follow the qualification requirements and formal guidelines for university degrees in teacher education. All student teachers complete a five-year research-intensive master’s degree in order to receive a formal teacher qualification. They are educated by academic teacher educators who are active researchers in teacher education. Teacher education is highly appreciated, the entrance is highly competitive and only the best applicants are selected to study in teacher education programs. Although Finnish teacher education has its unique characteristics, it has always been in interaction with international research and educational policy trends related to teacher education. During its existence, it has experienced the influences of practice turn, research turn and quite recently perhaps the first waves of accountability turn (cf. Cochran-Smith, M. (2016). Foreword. In G. Beauchamp, L. Clarke, C. Daly, M. Hulme, A. Jephcote, G.M., Kennedy, I. Menter, T. Murray, T. Mutton, T. O’Doherty & G. Peiser (Eds), Teacher Education in times of change–Responding to challenges across the UK and Ireland (pp. x-xiii). Policy Press.), and they have been realized in a specific way in Finnish teacher education and educational policy context. This chapter explores the development of Finnish teacher education, strengths, challenges, and research through these internationally identified “turns” as broader theoretical framing lenses.
Teacher Education Policy and Research: Global Perspectives